Allergic response to nasal administration of dexpanthenol in a child. A case report and a review of the literature - Turski, Mikołaj; Łukasiewicz, Małgorzata; Sajdak, Piotr; Ziajor, Seweryn; Bednarski, Artur; Tomasik, Justyna; Stodolak, Marcel (Alergologia Polska - Polish Journal of Allergology, 2024)
A 2-year-old boy with suspected lactose intolerance developed an extensive, itchy rash after using a nasal spray containing dexpanthenol. He was initially treated for a viral upper airway infection with ibuprofen, xylometazoline, and cetirizine. A switch to a drug containing dexpanthenol led to the appearance of the rash and subsequent sleep deprivation. No other possible cause of allergy was found. The withdrawal of all drugs but cetirizine led to full recovery. Dexpanthenol, an alcohol analog of vitamin B5, is present in many drugs for its positive impact on tissue repair. Although generally considered safe, it may rarely cause an allergic reaction, hence we underscore the importance of considering dexpanthenol oversensitivity in patients with unexplained widespread rashes, particularly in pediatric cases.